The governance gap: Preparing professions for digital transformation - Sean McDonald; Ben Gansky (Centre for International Governance Innovation (CIGI), 2023)
How do professional governance organizations teach their members, such as those who work in health care, law or urban planning, how to navigate digital transformation in their fields of practice? This paper looks at the governance gap created by the increasing role of digital technology in regulated professions, the participation process for setting professional standards and the education infrastructure to teach new professionals how to navigate both. The authors' recommendations focus on the role of professional education programs (degree-granting programs that train students to become a certified professional). The authors argue that bridging the gap between digitally transformed professional practice and professional governance will require training new professionals to do so.
Keywords: 330